2022
DOI: 10.3390/ijms23074005
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Blood Serum Extracellular Vesicles in Plaque Psoriasis and Psoriatic Arthritis Patients Reveals Potential Disease Biomarkers

Abstract: Psoriasis vulgaris (PsV) and psoriatic arthritis (PsA) are inflammatory diseases with unresolved pathophysiological aspects. Extracellular vesicles (EVs) play an important role in intercellular communication. We compared the miRNA contents and surface proteome of the EVs in the blood serum of PsV and PsA patients to healthy controls. Size-exclusion chromatography was used to isolate EVs from the blood serum of 12 PsV patients, 12 PsA patients and 12 healthy control subjects. EV samples were characterized and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 112 publications
(118 reference statements)
0
7
0
Order By: Relevance
“… 122 miRNAs seem to play a key role also in psoriatic arthritis (PsA) as suggested by Lättekivi et al who compared the miRNA in 12 psoriasis patients, 12 PsA patients and 12 healthy control subjects founding 212 different miRNAs in both psoriasis and PsA groups compared with healthy cohort. 123 A possible therapeutic approach using miRNAs was reported by Wu et al who showed that both miR-210 ablation in mice and inhibition of miR-210 by intradermal injection of antagomir-210 blocked the immune imbalance and the development of psoriasis-like inflammation in an imiquimod-induced or IL-23-induced psoriasis-like mouse model. 124 Thus, miRNAs seem to be promising biomarkers of prognosis, diagnosis and treatment response in psoriasis.…”
Section: Methodsmentioning
confidence: 99%
“… 122 miRNAs seem to play a key role also in psoriatic arthritis (PsA) as suggested by Lättekivi et al who compared the miRNA in 12 psoriasis patients, 12 PsA patients and 12 healthy control subjects founding 212 different miRNAs in both psoriasis and PsA groups compared with healthy cohort. 123 A possible therapeutic approach using miRNAs was reported by Wu et al who showed that both miR-210 ablation in mice and inhibition of miR-210 by intradermal injection of antagomir-210 blocked the immune imbalance and the development of psoriasis-like inflammation in an imiquimod-induced or IL-23-induced psoriasis-like mouse model. 124 Thus, miRNAs seem to be promising biomarkers of prognosis, diagnosis and treatment response in psoriasis.…”
Section: Methodsmentioning
confidence: 99%
“…21 Although there was no correlation between the total amount of serum EVs and the severity of psoriasis, the potential of EVs as diagnostic biomarkers for comorbidities is under investigation. 16,22 EVs also have potential as carriers for miRNAs and other targeted medicines for the treatment of psoriasis. 23 In this review, we mainly focus on EVs derived from skin-related cells and summarize their roles and possible functions in the pathogenesis of psoriasis (Figure 1), with the aim of determining novel future research directions for clinical and scientific research in the field of psoriasis.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…• The effects of adipose-derived EVs in psoriasis remain unclear potential of EVs as diagnostic biomarkers for comorbidities is under investigation. 16,22 EVs also have potential as carriers for miRNAs and other targeted medicines for the treatment of psoriasis. 23 We categorized skin derived EVs based on their specific cellular origins and reviewed their roles in the pathogenesis of psoriasis (Table 1).…”
Section: Adipose-derived Evsmentioning
confidence: 99%
See 2 more Smart Citations